Can “Closer-to-Nature” Forest Management Sustain Biodiversity and Ecosystem Services in an Uncertain Future? Lessons from Central Europe - Ana Stritih; Judit Lecina-Diaz; Johannes Mohr; Christian Schattenberg; Christian Ammer; Nicolò Anselmetto; Jürgen Bauhus; Andrej Bončina; Matteo Garbarino; Tomáš Hlásny; Marcus Lindner; Emanuele Lingua; et al. (Current Forestry Reports, 2026)
Purpose of Review Forests produce timber, mitigate climate change and provide important habitats; yet their capacity to provide these services under rapid global change is uncertain. “Closer-to-nature” forest management (CNFM) has been proposed by the EU Forest Strategy as a way to reconcile competing demands on forests while enhancing their resilience, but experiences with its implementation remain limited. We synthesized expert knowledge about CNFM in Central Europe, a region with a history of diverse forest management practices that has recently experienced severe impacts of climate change. We used a two-stage Delphi approach (including a questionnaire and a workshop) with experts in forest ecology and management to find a consensus about the effects of specific CNFM tools, and to identify knowledge gaps, barriers, and good practice examples of CNFM. Recent Findings A wider implementation of CNFM is likely to benefit biodiversity and ecosystem services under climate change, with only one clear trade-off identified between setting areas aside and wood production. However, limited empirical evidence exists for many of the expected effects. Substantial obstacles hinder the implementation of CNFM, including administrative constraints, social barriers, and gaps in knowledge and education. Nonetheless, we identified numerous successful cases of CNFM implementation from local to national scales in Central Europe. Summary CNFM is viewed as a potent strategy to navigate future social and ecological uncertainties, including large-scale disturbances. However, the implementation of CNFM should be adapted to the local context and ensure landscape-scale heterogeneity. Existing good practices could serve as examples for mainstreaming CNFM in Central Europe and beyond.